Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13104-018-3519-y
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Parental attitudes and knowledge on routine childhood immunization: an experience from Central Sri Lanka

Abstract: ObjectivesA lack of correct awareness about immunization among parents put them at risk of falling prey to the anti-vaccine movement. This risk is present even in countries with a high vaccine uptake. This study was done with the objective of assessing the awareness of parents childhood vaccination.ResultsIn this study conducted among 141 parents accompanying children to a routine clinic we found that 53.2% of the participants had average or above average knowledge. Level of knowledge was associated with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…This was also shown in a previous Lebanese study where having a private insurance resulted in higher rates of vaccination [ 9 ]. At last, our results go with the literature to prove that having more knowledge about the efficacy of vaccines, and having a positive attitude towards vaccination and its benefits, all will increase vaccination rates [ 15 , 34 ].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This was also shown in a previous Lebanese study where having a private insurance resulted in higher rates of vaccination [ 9 ]. At last, our results go with the literature to prove that having more knowledge about the efficacy of vaccines, and having a positive attitude towards vaccination and its benefits, all will increase vaccination rates [ 15 , 34 ].…”
Section: Discussionsupporting
confidence: 71%
“…Our results showed that 757 (27.2%) had good knowledge towards children’s vaccination. A study done in Sri Lanka showed that 44.0% of the participants had above average, 9.2% had average and 46.8% had below average knowledge [ 34 ]. The majority of the participants (90.1%) thought that vaccinating their children is very important, did not delay or plan to delay a vaccine and 3.5% of the participants stated that they were not in favor of vaccination despite bringing their children to get vaccinated [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The overall Knowledge attitude and practice was good among most of the parents (87.2%) in a study by Habib et al 19 Similarly, in a study conducted in Bangladesh, most participants (90.1%) thought that immunizing their children was very essential and did not delay or plan to delay any vaccine. 20 The present study results reflected that the majority of the caregivers believed that the antenatal clinics were the most trusted source of information about immunization and thought that the initiation of the immunization schedule should start right from birth. The study conducted by Adeyinka et al found that 65.7% of the respondents got information about VPDs from antenatal clinics.…”
Section: Discussionsupporting
confidence: 51%